Psychological Openness and the Emergence of Breakthrough vs. Incremental Innovations: A Regional Perspective. (8th August 2022) - Mewes, Lars; Ebert, Tobias; Obschonka, Martin; Rentfrow, P. Jason; Potter, Jeff; Gosling, Samuel D.
Abstract: Breakthrough innovations are expected to have a bigger impact on local economies than incremental innovations do. Yet past research has largely neglected the regional drivers of breakthrough innovations. Building on theories that highlight the role of personality psychology and human agency in shaping regional innovation cultures, we focus on psychological openness as a potential explanation for why some regions produce more breakthrough innovations than others do. We use a large data set of psychological personality profiles (∼1.26M individuals) to estimate the openness of people in metropolitan statistical areas (MSAs) in the US. Our results reveal that psychological openness is strongly associated with the emergence of breakthrough innovations but not with the emergence of incremental innovations. The findings remained robust after controlling for an extensive set of predictors of regional innovation such as star inventors, star scientists, or knowledge diversity. The results held even when we used tolerance as an alternative indicator of openness. Taken together, our results provide robust evidence that openness is relevant for regional innovation performance, serving as an important predictor for breakthrough innovations but not for incremental innovations.